A comparative insight into the oxidative damage and cell death potential of photoilluminated aminophylline – riboflavin system in normal and cancer lung cells of swiss albino mice. (December 2019) - Khan, Saniyya; Naseem, Imrana
Abstract: Photosensitisation of riboflavin (Rf) activates aminophylline (Am) resulting into the formation of a highly pro-oxidant Am-Rf system. We have previously shown its macromolecular damaging response in human peripheral lymphocytes, however, its potential inside a cancer cell is yet to be explored. Since, altered redox status of a cancer cell is a reliable therapeutic window in designing anticancer strategies, therefore, it's imperative to investigate whether the reactive oxygen species (ROS) generated by this system readily triggers apoptosis or it is countered by elevated antioxidant machinery of a cancer cell. Here, we have demonstrated DNA damaging and cytotoxic potential of this system in benzopyrene induced lung carcinoma cells. Using various biochemical assays significant macromolecular damage was observed along with mitochondrial membrane disruption as evaluated by rhodamine 6G membrane permeant. The 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl tetrazolium bromide (MTT) assay showed decreased cell viability, confirming cytotoxic action whereas fluorescence and electron microscopic evaluation confirmed apoptosis. ROS scavengers ameliorated the oxidative damage and inhibited cell death, thus confirming, pivotal role of ROS in causing cell death. It was evidently found out that the lung cancer cells were more sensitive towards the photodynamic action of this system, which can be attributed to the upregulated riboflavin metabolism in cancer cell. Hence, we propose a photodynamic mechanism to kill lung cancer cell that exhibits enhanced sensitivity towards cancer cells. Graphical abstract: Unlabelled Image Highlights: Photosensitized riboflavin activates aminophylline photochemistry. Am-Rf photocatalytic system generates burst of ROS. Generated ROS induces oxidative stress and DNA damage. System induces apoptotic cell death with increased sensitivity towards cancer cell. Increased sensitivity can be attributed to the upregulated Rf metabolism.